Business practice in the digital era : conference proceedings : UM FBA Asian Business Conference, 14 & 15 April 2005, Grand Plaza Parkroyal, Kuala Lumpur - UM FBA Asian Business Conference (2005 : Kuala Lumpur); Abdul Razak Ibrahim; Ezlika Ghazali (Kuala Lumpur : Universiti Malaya, 2005)
Contained conference papers in PDF format
Keywords: Electronic commerce -- Congresses; Information technology -- Economic aspects -- Congresses